2019
DOI: 10.1111/myc.12986
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of 15 antifungal drugs against a large collection of clinical isolates of Microsporum canis

Abstract: Summary Background Microsporum canis is a zoophilic species, found to be the most frequently isolated species in animals. M. canis causes sporadic outbreaks of infections in humans, such as the one that occurred in Canada, where more than 1000 human cases were detected over an 8‐year period. Despite the medical importance of M. canis infections, there are limited in vitro data on the antifungal susceptibility to antifungal drugs, including new generation triazoles and imidazoles. Objective The aim of the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 34 publications
5
24
3
Order By: Relevance
“…Terbinafine has also been one of the drugs of choice for the treatment of human and animal dermatophytosis, particularly tinea capitis, in recent years . Although full resistance to terbinafine has recently been reported in T. interdigitale and T. rubrum isolates, no terbinafine‐resistant T. verrucosum isolates have been documented .…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Terbinafine has also been one of the drugs of choice for the treatment of human and animal dermatophytosis, particularly tinea capitis, in recent years . Although full resistance to terbinafine has recently been reported in T. interdigitale and T. rubrum isolates, no terbinafine‐resistant T. verrucosum isolates have been documented .…”
Section: Discussionmentioning
confidence: 74%
“…An alarming trend of recalcitrant dermatophyte infections in Europe has been noted recently, which may be related to inadequate or discontinued treatment, difficulties in eliminating predisposing factors in hosts or infection sources, and frequent reinfections . In scientific literature, there are not many data available regarding drug resistance in dermatophytes, but it is suggested that the resistance is on the rise .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations